Behavioral effects of adult male mice induced by low-level acetamiprid, imidacloprid, and nicotine exposure in early-life - Saito, Hirokatsu; Furukawa, Yusuke; Sasaki, Takahiro; Kitajima, Satoshi; Kanno, Jun; Tanemura, Kentaro (Frontiers in Neuroscience, 2023)
Introduction Acetamiprid (ACE) and imidacloprid (IMI), the neonicotinoid chemicals, are widely used as pesticides because of their rapid insecticidal activity. Although these neonicotinoids exert very low toxicity in mammals, the effects of early, low-level, chronic exposure on the adult central nervous system are largely unclear. This study investigated the effects of low-level, chronic neonicotinoids exposure in early life on the brain functions of adult mice, using environmentally relevant concentrations. Methods We exposed mice to an acceptable daily intake level of neonicotinoids in drinking water during the prenatal and postnatal periods. Additionally, we also exposed mice to nicotine (NIC) as a positive control. We then examined the effects on the central nervous system in adult male offspring. Results In the IMI and NIC exposure groups, we detected behavior that displayed impairment in learning and memory. Furthermore, immunohistochemical analysis revealed a decrease in SOX2 (as a neural stem cell marker) and GFAP (as an astrocyte marker) positive cells of the hippocampal dentate gyrus in the IMI and NIC exposure groups compared to the control group. Discussion These results suggest that exposure to neonicotinoids at low levels in early life affects neural circuit base formation and post-maturation behavior. Therefore, in the central nervous system of male mice, the effects of low-level, chronic neonicotinoids exposure during the perinatal period were different from the expected effects of neonicotinoids exposure in mature animals.